Rubber Dam: Design and Construction Aspect for Pune: Exploring the Potential of Rubber Dam for Flood Control and Water Management in Pune (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The research was set with the objective of investigating the possibilities of constructing the rubber dam compared with the traditional dam. The rubber dam concept is relatively new in construction technology in India. Rubber dam concept is application wise used in the specific cases where it may be prove to be alternative, very few countries are widely developed rubber dam like Australia , china, Japan. Rubber dam has many advantages from various aspects like Irrigation, water supply, flood control, groundwater recharge, electric generation in hilly areas and water storage. Due to simple sophisticated design and its construction time is less as compared to conventional dam construction. Rubber dam is a useful technology, which can control water in flexible way. It is important and priority in urban and rural sector not only for irrigation but also industrial and for daily use. Rubber dam can minimize the crisis of flood and maximize the proper use of available water resources. This paper aims to study different flood hazardous, dry areas where rubber dam can be used in Pune and also point out the general description of system various configuration and types, working principle and comparative analysis between rubber dam and conventional dam.